Analysis of the impact of inflation on dollarization in the Iraqi economy for the period (2004-2022) (Entrepreneurship Journal for Finance and Business, 2024)
The Iraqi economy has known the phenomenon of foreign currency substitution since the eighties, with the increasing deterioration of the value of the Iraqi dinar and the appearance of signs of rapid inflation. Its actual expansion began with the phase of imposing the economic blockade in the nineties. Despite the decline in inflation rates following the phase of the economic blockade, the political, economic, and security turmoil After 2004, it was negatively affected by high inflation rates, especially during the period (2004-2007), which was reflected in the use of the US dollar as a tool to measure future payments, then a store of value, and then a medium of exchange in transactions that take place locally. Our study attempts to identify the phenomenon of foreign currency substitution in all its meanings and its relationship to inflation. Verifying the phenomenon of foreign currency substitution and determining its reality in the Iraqi economy during the period (2004-2022) In order to achieve the goal, the study adopted the inductive approach in analyzing the phenomenon under study, used the descriptive analysis method, and chose the correlation model to analyze the data and reach the results. After following the International Monetary Fund index in measuring foreign currency substitution represented by dividing deposits in foreign currency by the broad money supply, the study concluded There is a direct relationship between the inflation rate and the rate of foreign currency replacement in the Iraqi economy, with a strong direct correlation rate of (0.70) Therefore, the phenomenon of foreign currency substitution must be taken into consideration and the necessary measures taken to reduce it, especially through policies to stabilize inflation rates at low levels and search for another way to price crude oil instead of the US dollar, and let it be a basket of foreign currencies in order to reduce the linkage of the Iraqi economy to the dollar